2019
DOI: 10.1111/acer.13976
|View full text |Cite
|
Sign up to set email alerts
|

p53‐Mediated Activities in NS‐5 Neural Stem Cells: Effects of Ethanol

Abstract: Background: Transforming growth factor (TGF) b1 and ethanol (EtOH) powerfully inhibit the proliferation, DNA repair, and survival of neural stem cells (NSCs). The present study tests the hypothesis that the EtOH-induced DNA damage response is mediated through p53 pathways and influenced by growth factor signals.Methods: Cultures of nonimmortalized NSCs, NS-5 cells, were transfected with p53 siRNA, exposed to either the mitogenic fibroblast growth factor (FGF) 2 or antimitogenic TGFb1, and to EtOH. Stage-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Alcohol’s induction of nucleolar stress offers insight into its known ability to induce p53 in diverse neural lineages, including those derived from the cortex [ 45 ], somatosensory cortex [ 25 ], dorsal root ganglia [ 46 ], and immortalized NSCs [ 43 , 47 ], as well as cranial neural crest cells [ 23 , 24 , 48 ]. This is accompanied by the up-regulation of p53-dependent pathways [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol’s induction of nucleolar stress offers insight into its known ability to induce p53 in diverse neural lineages, including those derived from the cortex [ 45 ], somatosensory cortex [ 25 ], dorsal root ganglia [ 46 ], and immortalized NSCs [ 43 , 47 ], as well as cranial neural crest cells [ 23 , 24 , 48 ]. This is accompanied by the up-regulation of p53-dependent pathways [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that EtOH causes DNA damage and increases p53. (33) Since p53 is known to enhance transcription of DUSP6, (34) the p53-DUSP6 pathway may be involved in EtOH induced DUSP6 expression. However, DUSP6 expression is reduced in the cerebral cortex of rats exposed to EtOH vapor for 7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The above effect was more obvious for NSCs treated with TGFβ‐1 (Hicks & Miller, 2019). Similarly, another study revealed that ethanol and TGFβ‐1 induced changes in the number of proliferating NSCs were significantly enhanced after NSCs treatment with p53 siRNA (Miller, 2019). The experiment illustrated the synergistic actions of TGFβ‐1 and ethanol in inducing DNA damage and triggering DDR.…”
Section: Nscs Regulate Factors Related To Dna Damage Repairmentioning
confidence: 91%